2018
DOI: 10.3389/fcvm.2018.00136
|View full text |Cite
|
Sign up to set email alerts
|

CD100 Effects in Macrophages and Its Roles in Atherosclerosis

Abstract: CD100 or Sema4D is a protein from the semaphorin family with important roles in the vascular, nervous and immune systems. It may be found as a membrane bound dimer or as a soluble molecule originated by proteolytic cleavage. Produced by the majority of hematopoietic cells including B and T lymphocytes, natural killer and myeloid cells, as well as endothelial cells, CD100 exerts its actions by binding to different receptors depending on the cell type and on the organism. Cell-to-cell adhesion, angiogenesis, pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…It is well established that Sema4D and its receptors are expressed in various cell types, including macrophages, and Sema4D has been suggested to be associated with macrophage polarization. 42 A recent study found that Sema4D not only promoted endothelial cell adhesion and migration but also enhanced lactic acid release and induced M2 polarization of macrophages. 43 Another study demonstrated correlations between Sema4D expression and M2 macrophage counts in primary tumors, as well as M2 macrophage percentages in ascites.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that Sema4D and its receptors are expressed in various cell types, including macrophages, and Sema4D has been suggested to be associated with macrophage polarization. 42 A recent study found that Sema4D not only promoted endothelial cell adhesion and migration but also enhanced lactic acid release and induced M2 polarization of macrophages. 43 Another study demonstrated correlations between Sema4D expression and M2 macrophage counts in primary tumors, as well as M2 macrophage percentages in ascites.…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports focused on sCD100/mCD100 regulation to T cell function in AMI patients. The extracellular domain of CD100 retained biological activity after shedding from immune cell surface upon activation, resulting in the alteration of macrophage differentiation and phenotype in atherosclerosis [ 13 ] and facilitation of CD8 + T cells activity in chronic hepatitis [ 14 , 33 ]. Thus, sCD100 that is shed from CD8 + T cells in turn promoted CD8 + T cell cytotoxicity, further demonstrating the consequences of CD8 + T cells activation in AMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…CD100 could be produced by majority of hematopoietic cells, and functions as a ligand by binding to receptors depending on the cell types, including CD72 on lymphoid tissues and plexin B1/B2 on non-lymphoid tissues [ 11 ]. Plaque marcophages and foam cells in human atheomas also express CD100 [ 12 ], which contributes to marcophages-mediated inflammation in atheroscleriosis [ 13 ]. Two forms of CD100 could be found as a membrane-bound dimer (mCD100) or as a soluble molecule (sCD100) originated via proteolytic cleavage by certain factors, especially matrix metalloproteinases (MMPs) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as a chronic inflammatory condition marked by the development of arterial sclerosis and the release of inflammatory substances secreted by macrophages. Macrophages via its secretions orchestrate the immune response in atherosclerosis [4].…”
Section: Introductionmentioning
confidence: 99%